Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/ele.12564
|View full text |Cite
|
Sign up to set email alerts
|

Host dispersal as the driver of parasite genetic structure: a paradigm lost?

Abstract: Understanding traits influencing the distribution of genetic diversity has major ecological and evolutionary implications for host-parasite interactions. The genetic structure of parasites is expected to conform to that of their hosts, because host dispersal is generally assumed to drive parasite dispersal. Here, we used a meta-analysis to test this paradigm and determine whether traits related to host dispersal correctly predict the spatial co-distribution of host and parasite genetic variation. We compiled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 65 publications
2
100
1
Order By: Relevance
“…(hosts for specialist mites) show a much higher average level of mtDNA population differentiation (F st  = 0.95, P  < 0.05) when compared to M. coucha (most mobile hosts for the generalist mite) (F st  = 0.36, P  < 0.05). Although the data here support the paradigm that parasite genetic structure depends on host dispersal [42], it is well documented that parasite life history [14, 43, 44] and abiotic factors [45] can equally influence parasite population differentiation. Since the majority of life history characteristics of the two Laelaps species used in our study are very similar [6, 23], and both species were most likely exposed to similar abiotic factors in their overlapping ranges (with eight identical sampling localities), we can most likely attribute the differences in population genetic structure of the parasites to either differences in life histories of the hosts, host dispersal ability, or species specificity of the parasite (or a combination of these three).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…(hosts for specialist mites) show a much higher average level of mtDNA population differentiation (F st  = 0.95, P  < 0.05) when compared to M. coucha (most mobile hosts for the generalist mite) (F st  = 0.36, P  < 0.05). Although the data here support the paradigm that parasite genetic structure depends on host dispersal [42], it is well documented that parasite life history [14, 43, 44] and abiotic factors [45] can equally influence parasite population differentiation. Since the majority of life history characteristics of the two Laelaps species used in our study are very similar [6, 23], and both species were most likely exposed to similar abiotic factors in their overlapping ranges (with eight identical sampling localities), we can most likely attribute the differences in population genetic structure of the parasites to either differences in life histories of the hosts, host dispersal ability, or species specificity of the parasite (or a combination of these three).…”
Section: Discussioncontrasting
confidence: 48%
“…The complexity and diversity of parasite systems, however, render accurate predictions on the factors responsible for parasite dispersal problematic. For example, host dispersal is not consistently correlated with parasite movement [14], parasites with broad host ranges can be highly structured due to biogeographic influences [15], and even obligate host-specific parasites do not necessarily show significant co-evolutionary patterns [5]. Through concerted efforts, however, some generalizations emerge such as the specialist-generalist variation hypothesis (SGVH) as proposed by Li et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been shown that a strong link between host dispersal and parasite genetic structure is not ubiquitous, and depends on factors that include the degree of association with the host and host mobility [10]. Here, we investigated spatial genetic structure and past demography of an ectoparasite that is associated with highly mobile flying hosts, and would be considered a weak generalist based on its association with a number of different host species that are closely related to each other [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigated spatial genetic structure and past demography of an ectoparasite that is associated with highly mobile flying hosts, and would be considered a weak generalist based on its association with a number of different host species that are closely related to each other [10]. Our study complements a body of work on spatial genetic structure and phylogeography of various ectoparasites associated with hosts having higher mobility [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect population genetic methods overcome this limitation by characterizing historical patterns of dispersal in host genomes, raising the possibility that host genetic structure could forecast the pathways of invading pathogens. However, host genetic structure may not correlate with pathogen spread because of the different timescales reflected in host and pathogen genomes or if infection alters host dispersal behavior (3,4). Differences among genomes in modes of inheritance might also influence genetic forecasts of pathogen spread.…”
mentioning
confidence: 99%